2007
DOI: 10.1158/1078-0432.ccr-06-2613
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Mutations Are a Late Event in the Progression of Head and Neck Squamous Cell Cancer

Abstract: Purpose:To determine the timing of mitochondrial mutations in the progression of head and neck squamous cell carcinoma. Experimental Design:Twenty-three mitochondrial mutations were identified in 12 tumors using a high-throughput mitochondrial sequencing array. Areas of adjacent dysplastic and normal epithelium adjacent to tumors were sequenced using conventional methods for the presence of mutations that occurred in the corresponding tumor. Results: Two of 23 (8.7%) tumor mitochondrial mutations (2 of 12 tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…Their occurrence seems to be rather late e.g. in head and neck cancers [84]. For BC no comparable data of significant series of patients are available, which would allow a precise analysis of this aspect.…”
Section: Molecular Follow-up In Urinary Bladder Carcinomamentioning
confidence: 99%
“…Their occurrence seems to be rather late e.g. in head and neck cancers [84]. For BC no comparable data of significant series of patients are available, which would allow a precise analysis of this aspect.…”
Section: Molecular Follow-up In Urinary Bladder Carcinomamentioning
confidence: 99%
“…Mutations in D-loop region and ∼5 kb deletion in mtDNA have also been implicated to increase ROS production, which may be driving force for tumorigenesis [18][19][20][21][22]. Few reports suggested an increase in D-loop somatic mutations in cancer tissue [23,24], while some studies found ∼5 kb deletion to be more prevalent in precancerous lesion or adjacent non-cancerous tissues than in malignant cancerous tissue [25][26][27]. But comparative study of mtDNA contents and mutations in oral cancer and precancer tissues are very few.…”
Section: Introductionmentioning
confidence: 99%
“…1). Over a decade before Lucas was born, Otto Warburg, in 1931, observed that cancer cells consume oxygen via mitochondrial oxidative phosphorylation at much higher rates than normal cells and hypothesized that cancer was actually the result of mitochondrial defects (2).…”
mentioning
confidence: 99%
“…A gene array chip is now commercially available that can sequence the mitochondrial genome in just 48 h. A derivative of this relative facility in sequencing is the creation of a public database of mtDNA population variation in human evolution and disease, the MITOMAP. 1 This internet-based tool provides the user-detailed information on mtDNA sequence, function, polymorphisms, haplogroups, and mutations-both germ line and somatic associated with disease states.…”
mentioning
confidence: 99%